2016
DOI: 10.1109/tcpmt.2015.2499767
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Emerging Bonded Interface Materials for Large-Area Attachments

Abstract: NREL prints on paper that contains recycled content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Paret et al studied the reliability of DBC-Copper plates with an area of 50.8 mm à 50.8 mm. Test results proved that sintered-silver samples failed after subsequent thermal cycling 2,300 cycles between À40°C and 150°C (Paret et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Paret et al studied the reliability of DBC-Copper plates with an area of 50.8 mm à 50.8 mm. Test results proved that sintered-silver samples failed after subsequent thermal cycling 2,300 cycles between À40°C and 150°C (Paret et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…However, there are limited studies reporting low-pressure-sintered silver as bonding interface materials for large-area and super-large-area bonding processes (Tan et al, 2018). So far, the most widely acceptable super-large-area bonding process was applying a high pressure (30-40 MPa) to obtain sintering of pre-dried silver particles or flakes at a temperature lower than 300°C (Paret et al, 2016;Schwarzbauer and Kuhnert, 1989). Narumanchi et al (2011) reported on silver-sintered DBC-Copper plates with a super-large area of 50.8 mm à 50.8 mm power dies bonded at 280°C and 30 MPa for a few minutes, whereas the edges of samples showed poor bonding areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these materials, sintered silver, along with transient liquid-phase bonding, is a leading candidate for replacing solders in novel power electronics packaging designs. In the past, sintered silver made from micron-sized silver particles demonstrated excellent reliability under accelerated thermal cycling conditions [1]. However, the drawback of the high bonding pressure (30 -40 MPa) requirement resulted in its limited applications and necessitated the research and development of novel and simple bonding techniques of sintered silver.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, research at the National Renewable Energy Laboratory (NREL) was focused on characterizing the reliability of sintered silver joints synthesized from micronsized silver particles [1]. Accelerated thermal cycling from -40°C to 150°C was conducted on 50.8-mm x 50.8-mmfootprint test samples, in which Si3N4 substrates were bonded to copper baseplates with sintered silver material.…”
Section: Introductionmentioning
confidence: 99%